2021
DOI: 10.1007/s00787-020-01689-z
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of dysregulation in preschool age

Abstract: Background: Dysregulation of emotions, behaviour and attention are involved in several areas of childhood psychopathology, but knowledge about early developmental trajectories remains scarce. This study aims to explore continuity and associations of dysregulation in preschool age.Methods: Dysregulation was measured at age 2½ years and again at 5 years in a community-based birth cohort of 1,099 children using the Child Behavior Checklist, preschool version (CBCL1½-5), answered by mothers. Based on the CBCL-DP/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…In this study, CBCL-DP associations with prematurity are comparable to prior studies using similar measures related to behavioral problems at 6 to 19 years . Across GA groups, our results are also consistent with multinational findings regarding CBCL-DP trajectories associated with individual psychosocial adversities …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, CBCL-DP associations with prematurity are comparable to prior studies using similar measures related to behavioral problems at 6 to 19 years . Across GA groups, our results are also consistent with multinational findings regarding CBCL-DP trajectories associated with individual psychosocial adversities …”
Section: Discussionsupporting
confidence: 90%
“…Emotional and behavioral dysregulation among school-aged children has an average multinational prevalence of 9% (range, 2%-18%; n = 56 666) and is associated with subsequently severe behavioral, affective, and cognitive impairments through adulthood . Risk factors for children’s persisting emotional and behavioral dysregulation involve the cumulative burden of medical and socioeconomic adversities, as well as parental psychological and substance use challenges …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two birth cohorts in China, prevalences of 6.4% [41] and 12.3% [42] were reported for children 3 and 4 years old, respectively, although they evaluated the prevalence of Attention-Deficit-Hyperactivity Disorders (ADHD) while we evaluated only attentional function-just one of the ADHD symptoms. In another birth cohort study from Denmark, a prevalence of 30% was reported for children of 5 years [43]. Thus, it is difficult to make comparisons of inattention prevalence among studies since specific cut-off points or definitions for inattention are not used consistently yet.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of MDS on children’s sleep and behavioral adjustment during the preschool period is not likely to be less important than during infancy and other developmental stages. Nevertheless, the vast majority of relevant studies has focused on the impact of postpartum depressive symptoms in the first few months to 3 years after childbirth (e.g., Ystrom et al, 2017 ; Parade et al, 2019 ; Cook et al, 2020 ; Asmussen et al, 2021 ). Given the importance of early childhood as a transition from infancy to middle childhood in both sleep and behavioral adjustment and the observed developmental changes during this period, understanding how these processes change over time in relation to MDS is crucial.…”
Section: Introductionmentioning
confidence: 99%